Hydroxyl defect effect on the resistance degradation behavior in Y-doped (Ba, Ca)(Ti, Zr)O3 bulk ceramics. Issue 13 (October 2016) - Kao, Y.J.; Huang, C.Y.; Su, C.Y.; Pithan, C.; Hennings, D.F.; Waser, R.
Abstract: Degradation behavior of acceptor (Y)-doped (Ba, Ca)(Ti, Zr)O3 ceramics sintered in moist reducing atmosphere and subsequently re-oxidized in dry or wet atmospheres was contrasted. The degradation behavior critically depends on the water vapor incorporation, the time to degradation systematically decreased with the incorporation of hydroxyl defects ( O H ) O . The electrical conductivity was investigated by means of impedance spectroscopy (IS) to determine properties, such as grain and grain boundary conductivity, grain boundary potential barrier height, and space charge layer thickness. Furthermore, transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) were applied to consider microstructure, microchemistry, and oxygen stoichiometry changes.